Alternative stents in ST-segment elevation myocardial infarction: improving the efficacy of primary percutaneous coronary intervention. (May 2015) - Yetgin, Tuncay; Nakatani, Shimpei; Onuma, Yoshinobu; van Geuns, Robert-Jan M
ABSTRACT : Despite the efficacy of primary percutaneous coronary intervention in achieving epicardial reperfusion in ST-segment elevation myocardial infarction, it is often limited by impaired microvascular perfusion attributable to distal embolization of plaque and thrombus, and stent malappostion due to vessel constriction and thrombus apposition, attenuating the full benefits of myocardial reperfusion and resulting in unfavorable clinical outcomes. In the long run implantation of permanent metallic implants have negative effect the biological behavior of the target vessel with a continuous low device failure over the years. Recently, however, efforts have been realized to tackle these shortcomings and optimize mechanical reperfusion by improvements to stent design, as substantiated by the self-expanding stent, the mesh-covered stent and the bioresorbable vascular scaffold. In this article, we provide an overview of the role of these novel, innovatively designed, alternative devices in patients undergoing primary percutaneous coronary intervention for ST-segment elevation myocardial infarction.